Transformative insights in breast cancer: review of atomic force microscopy applications - Jiamin Ma; Yuanyuan Zhai; Xiaoyi Ren; Huifang Wu; Mengjie Yang; Lijun Chai; Jianzhong Chen (Discover Oncology)
Abstract Breast cancer remains one of the foremost global health concerns, highlighting the urgent need for innovative diagnostic and therapeutic strategies. Traditional imaging techniques, such as mammography and ultrasound, play essential roles in clinical practice; however, they often fall short in detecting early-stage tumors and providing comprehensive insights into the mechanical properties of cancer cells. In this context, Atomic Force Microscopy (AFM) has emerged as a transformative tool in breast cancer research, owing to its high-resolution imaging capabilities and nanomechanical characterization. This review explores recent advancements in AFM technology as applied to breast cancer research, emphasizing key findings that include the differentiation of various stages of tumor progression through high-resolution imaging, precise characterization of mechanical properties, and the capability for single-cell analysis. These capabilities not only enhance our understanding of tumor heterogeneity but also reveal potential biomarkers for early detection and therapeutic targets. Furthermore, the review critically examines several challenges and limitations associated with the application of AFM in breast cancer research. Issues such as complexities in sample preparation, accessibility, and the cost of AFM technology are discussed. Despite these challenges, the potential of AFM to transform our understanding of breast cancer biology is significant. Looking ahead, continued advancements in AFM technology promise to deepen our insights into breast cancer biology and guide innovative therapeutic strategies aimed at improving patient outcomes.